Telaah Problematika Anak Slow Learner dalam Pembelajaran - Mansyur, Abd. Rahim (Education and Learning Journal, 2022)
This study reviews the problems of slow learnersÂ in learning. Literary references slow learner to teachers providing learning and parents in providing assistance to children at home during online learning. Based on the results of the study that has been carried out, it is concluded that slow learner children are children who experience learning delays. This can be shown in situations where a child has not been able to master the learning information conveyed by the teacher within a certain time limit. The characteristics of these children are one level above mentally retarded children so they need teacher responses and regular assistance to help them develop themselves. Teachers must observe and identify children who are slow learners to be given counseling assistance that can stimulate cognitive, affective, physical, and intuitive aspects. Counseling should also educate children to use devices in a positive way during online learning.